Anteseden Intensitas Penggunaan Layanan E-Wallet dan Dampaknya Terhadap Spending Behavior pada Generasi Millenial - Leasa, Simon Hendrik; Siaila, Steven; Ferdinandus, Stenly (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
This study aims to determine the effect of perceived ease of use, perceived usefulness and perceived credibility on the behavior of the intention to use e-wallet services and their impact on the spending behavior of the millennial generation in Ambon city. Respondents in this study were millennials who live in Ambon with a research sample of 100 respondents. This type of research is associative and the data source uses primary data. The data collection technique uses a questionnaire through the Google form. The collected data were then analyzed using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results of the study show that the shopping behavior of respondents in Ambon is influenced by the intensity of the intention to use e-wallet services. However, other findings show that perceived ease of use has a significant effect and perceived usefulness and perceived credibility do not have a significant effect on the intention to use e-wallet services. Then the limitations in this study are that the respondents who are involved are only the millennial generation. For this reason, it is hoped that further research can add other variables and add respondents from other generations.